2021
DOI: 10.1177/0269881120967878
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Psychological Insight Questionnaire among a sample of people who have consumed psilocybin or LSD

Abstract: Background: Several measures have been developed to examine acute psychedelic effects (e.g. mystical-type and challenging experiences), but no measure assesses acute psychologically insightful experiences that may occur during psychedelic experiences. Aim: The purpose of this study was to develop and examine the psychometric properties of the Psychological Insight Questionnaire. Method: A cross-sectional survey study among psilocybin and LSD users. Respondents ( n=1661; Mage=22.9, standard deviation=8.5; Cauca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 50 publications
3
79
2
Order By: Relevance
“… Lane and colleagues (2015) argue that for traumatization, the essential ingredients of therapeutic change include reactivating old memories and then engaging in new emotional experiences that are incorporated into these reactivated memories via the process of reconsolidation. Insight would then represent the natural product of this process which psychedelics appear to facilitate ( Davis et al, 2020 ; Davis et al, in press ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Lane and colleagues (2015) argue that for traumatization, the essential ingredients of therapeutic change include reactivating old memories and then engaging in new emotional experiences that are incorporated into these reactivated memories via the process of reconsolidation. Insight would then represent the natural product of this process which psychedelics appear to facilitate ( Davis et al, 2020 ; Davis et al, in press ).…”
Section: Discussionmentioning
confidence: 99%
“…(PIQ; Davis et al, 2020 ; Davis et al, in press ). The 23-item PIQ was included in the study to assess participants’ insights had during the psychedelic experience related to emotions, beliefs, memories, and relationships.…”
Section: Methodsmentioning
confidence: 99%
“…Results also showed that the acute psychedelic effects (mystical experience and emotional breakthrough) were associated with greater improvements in psychological flexibility. 55 Another report 56 showed that psychological insight (measured with the PIQ 30 ) was significantly correlated with retrospectively reported increases in psychological flexibility that occurred from pre- to postpsychedelic experience. Although emerging evidence suggests that acute insight experiences may be highly correlated with therapeutic outcomes, 23 , 30 it is important to consider that these effects usually occur in the context of a mystical-type experience and prior studies that have modeled this relationship have controlled for the moderate to large correlation between these variables.…”
Section: Introductionmentioning
confidence: 99%
“…In Western countercultures, psychedelics have also been historically related to antihegemonic revolutionary tendencies (Lee and Shlain, 1985). Such tendencies occurred as a result of fidelity to the LSD event, in an attempt to popularize psychedelics (Saldanha, 2007b) and/or-as we suggest here-through critical insights and revelations reached while under the influence of psychedelics (La Barre, 1938Barre, /1975Winkelman, 2010;Luna, 2011;Labate and Cavnar, 2014;Strassman, 2014;Davis et al, 2020Davis et al, , 2021. Regardless of the way in which they were induced, similar revelations are known to come with the enthusiasm to deliver the message to others, which at times developed into social movements (Mooney, 1896(Mooney, /1991Wallace, 1956;Lanternari, 1963;Whitehouse, 2004;Taves, 2016).…”
Section: Ayahuasca and Revelatory Eventsmentioning
confidence: 86%